An hybrid approach for primary energy balance of an existing waste-to-energy plant. (August 2018) - Maria, Francesco Di; Sisani, Federico; Lasagni, Marzio; El-Hoz, Mervat
Abstract: The ability of an existing waste-to-energy (WtE) plant for not hazardous waste in replacing primary energies was assessed in a preliminary way. For doing this a life cycle approach was adopted including the primary energies consumed by the plant due to chemicals and fuels needs and the one replaced by the recovery of electricity from the combustion of waste. For doing this the cumulative energy demand (CED) (MJ) index was used. Furthermore, by the aid of an hybrid approach the energy introduced in the plant by the waste was also accounted. Main results indicated that the CED (MJ) resulted always < 0 indicating that the primary energy replaced by electrical energy recovery was higher than the primary energies consumed by the plant by chemicals and fuels. By the way the hybrid approaches indicate that combined heat and power mode has to be preferred for WtE operation.